Dendritic Glycerol-Cholesterol Amphiphiles as Drug Delivery Systems: A Comparison between Monomeric and Polymeric Structures - Jocelyn Fernanda Romero; Svenja Herziger; Mariam Cherri; Mathias Dimde; Katharina Achazi; Ehsan Mohammadifar; Rainer Haag (MDPI AG, 2023)
The application of micelles as drug delivery systems has gained a great deal of attention as a means to overcome the current several drawbacks present in conventional cancer treatments. In this work, we highlight the comparison of polymeric and monomeric amphiphilic systems with a similar hydrophilic-lipophilic balance (HLB) in terms of their biocompatibility, aggregation behavior in aqueous solution, and potential in solubilizing hydrophobic compounds. The polymeric system consists of non-ionic polymeric amphiphiles synthesized via sequential RAFT polymerization of polyglycerol first-generation [G1] dendron methacrylate and cholesterol methacrylate to obtain poly(G1-polyglycerol dendron methacrylate)-block-poly(cholesterol methacrylate) (pG1MA-b-pCMA). The monomeric system is a polyglycerol second-generation [G2] dendron end-capped to a cholesterol unit. Both amphiphiles form spherical micellar aggregations in aqueous solution, with differences in size and the morphology in which hydrophobic molecules can be encapsulated. The polymeric and monomeric micelles showed a low critical micelle concentration (CMC) of 0.2 and 17 μg/mL, respectively. The results of our cytotoxicity assays showed that the polymeric system has significantly higher cell viability compared to that of the monomeric amphiphiles. The polymeric micelles were implemented as drug delivery systems by encapsulation of the hydrophobic small molecule doxorubicin, achieving a loading capacity of 4%. In summary, the results of this study reveal that using cholesterol as a building block for polymer synthesis is a promising method of preparation for efficient drug delivery systems while improving the cell viability of monomeric cholesterol.